VIEWS ON THE POLITICAL LEADER AND HIS EASTERN ESSENCE - Aҳмадхожайев , М.З (Educational Research in Universal Sciences, 2023)
This article highlights the political leader and his institutional formation in the cycle of primary society management until the status of the current developed era, and the oriental basis of this dogma as a legal term and the level of the psychology of the society of the eastern countries from the point of view of authority is highlighted